Research on Mercedes Benz marketing strategy of Hefei Yuanxing Automobile Service Co., Ltd - Wen, Haigang (International Journal of Management and Education in Human Development, 2022)
With the continuous improvement of Chinese people's income, their living standard has been greatly improved. It is almost common to buy vehicles. However, in recent years, the competition in the automobile market has become extremely fierce. This paper selects Hefei Yuanxing Automobile Service Co., Ltd. (hereinafter referred to as Yuanxing Benz) as the research object, and analyzes its marketing strategy through literature query and field investigation. SWOT is used to analyze the opportunities and threats in its external environment and the advantages and disadvantages of the enterprise itself. 4P marketing strategy is used to analyze the company's automotive products, prices, and promotions. Finally, it is suggested that the company should accurately locate, highlight product advantages, reasonably price and construct diversified marketing channels. The marketing mix, further, promotes the synchronous improvement of the company's product sales and profits.